Platelet-rich plasma and platelet-rich fibrin in periodontal regeneration: A review - Sunil Paramel Mohan (Journal of Pharmacy and Bioallied Sciences, 2019)
Platelet concentrates (PCs; platelet-rich plasma and platelet-rich fibrin) are autologous bioactive substances that have found varied application in medical and dental fields, particularly in oral and maxillofacial surgery, plastic surgery, and sports medicine. The rationale of these technologies is to extract all the elements from patient’s own blood sample, which could be used to improve healing by promoting tissue regeneration. PCs have evolved a long way since its introduction in 1954. PCs have been used successfully in periodontics and implant dentistry. However, the preparation protocol, processing time, transfer of concentrates, centrifugation temperature, vibration, etc., being not standardized are various factors for the mixed results reported in the literature. This review intends to discuss evolution of PCs, their preparation techniques, and their clinical and technical aspects and applications.